2021
DOI: 10.1177/00034894211028436
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Impact of USMLE Step 1 Score Reporting to Pass/Fail on Otolaryngology Applicant Selection

Abstract: Objectives: Recently, the decision was made to transition the United States Medical Licensing Examination (USMLE) Step 1 score from a three-digit numerical score to a pass/fail system. Historically, Step 1 scores have been important for otolaryngology resident applicant selection. The purpose of this study was to understand and evaluate otolaryngology residency program directors’ (OPDs) opinions on the impact following the change in Step 1 score reporting. Methods: A 22-question survey administered through Qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 10 publications
(12 reference statements)
1
18
0
Order By: Relevance
“…8 Because most medical schools have migrated to a pass-fail preclinical curriculum, the Step 2 CK examination will serve as the sole, universal, objective, comparative metric for future applicants. Complementary to previous literature suggesting that Step 2 CK scores will function as a surrogate of equal or higher importance to Step 1, 15,2126 our respondents indicated Step 2 CK performance as either the first or second most important factor for interview consideration. Excellent performance on Step 2 CK is now imperative, whereas in previous years an impressive score was supplemental or partially rectified a poor Step 1 score.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…8 Because most medical schools have migrated to a pass-fail preclinical curriculum, the Step 2 CK examination will serve as the sole, universal, objective, comparative metric for future applicants. Complementary to previous literature suggesting that Step 2 CK scores will function as a surrogate of equal or higher importance to Step 1, 15,2126 our respondents indicated Step 2 CK performance as either the first or second most important factor for interview consideration. Excellent performance on Step 2 CK is now imperative, whereas in previous years an impressive score was supplemental or partially rectified a poor Step 1 score.…”
Section: Discussionsupporting
confidence: 58%
“…Ironically, the resultant substantial implications of the Step 2 CK examination may have worsened the preexisting ‘Step mania’ that inspired the initial transition. 2326,27 Evaluation of data from future match cycles will better delineate the importance of Step 2 CK performance within the orthopaedic match.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 From an otolaryngology standpoint, recent studies have shown that most academic otolaryngologists (department chairs, program directors, and faculty) disagree with changing USMLE Step 1 scoring to pass/fail, believing that it will increase other metrics’ weight (eg, USMLE Step 2 CK, away rotation performance, grades in required clerkship rotations) and put certain student populations at a disadvantage (eg, international, osteopathic, and underrepresented minority students). 7,8 While program directors’ perspectives on the USMLE Step 1 score change have been examined to some extent, comparing the perspectives of medical students interested in otolaryngology, otolaryngology house-staff (resident and fellows), and otolaryngology program directors is needed to better understand the potential implications of the transition to pass/fail score reporting.…”
Section: Introductionmentioning
confidence: 99%
“…As such, less standardized factors such as research, other extracurriculars, and clerkship grades are suggested to become increasingly important in the residency application process. [3][4][5] Understandably, building a residency application around numerous criteria may contribute to applicant anxiety about applying to a selective specialty like otolaryngology. 1,3,6 Therefore, it becomes increasingly important to use evidence-based guidance to inform medical students who are considering otolaryngology as their specialty of choice; by highlighting trends in the qualifications of accepted applicants, prospective applicants can use a data-driven approach to focus on areas of their application more beneficial to their match.…”
mentioning
confidence: 99%